A Literature Review on China’s Population Aging, Human Capital and R&D Capital Stock - Zhu, Mingliang; Xu, Jie (Journal of Accounting, Business and Finance Research, 2019)
This paper mainly studies the impact of population aging on human capital, and combs the relevant literature. This paper compares the different status quo of population aging in China and abroad, and the different effects of population aging in different countries. We also want to know whether the aging of population affects the stock of R&D capital and whether this impact is brought about by the change of human capital. Through the existing literature, we find that population aging will directly lead to the reduction of R&D human capital stock, which is generally accepted by all countries. At the same time, the change of human capital brought by population aging brings about the change of education capital and health capital. But scholars have not yet reached a clear conclusion. Through the study of this conduction effect, we can further explore the mechanism of population aging.